Konseling ABCDE Seligman untuk Meningkatkan Optimisme Mahasiswa Pindah Jurusan - Eem Munawaroh; Binti Isrofin; Ulung Giri Sutikno (Universitas Sebelas Maret, 2018)
Transfer students required academic and social adaptation in new department. Therefore, transfer students often concerns about their academic success in the future. The purposes of This study was to examine the effectiveness of ABCDE counseling model to improve optimism of transfer students in Universitas Negeri Semarang. The research design was a mixed method with convergent parallel design type. The subjects of this study were three transfer students of Universitas Negeri Semarang obtained by purposive sampling technique. Data was collected by optimism scale that supports three aspects of optimism namely permanence, pervasiveness, and improvement. The ABCDE Seligmen counseling stages include Adversity, Belief, Consequences, Dispute, and Energization. Quantitative data analysis used is paired t test and qualitative data analysis was by analyzing verbatim counseling. The results of the study showed that counseling ABCDE Seligman was able to increase transfer students optimism significantly.